Vitreoretinal surgery in patients with intraocular lens dislocation into the vitreous (Annals of Medical Research, 2021)
Aim: To evaluate the demographic and clinical characteristics of patients who underwent pars plana vitrectomy (PPV) for intraocular lens (IOL) dislocation into the vitreous cavity and the visual and anatomical outcomes of PPV in these patients.Material and Methods: This retrospective study reviewed the files of patients who underwent PPV for IOL dislocation into the vitreous in our clinic between January 2014 and December 2018. Patient age, gender, preoperative and postoperative best corrected visual  acuity (BCVA), intraocular pressure (IOP), comorbid ocular pathologies, causes of IOL dislocation, time from IOL dislocation to PPV surgery, surgical methods, and preoperative and postoperative complications were recorded.Results: This study included 15 eyes of 15 patients with IOLs dislocated into the vitreous, of which 5 (33.3%) were female and 10 (66.7%) were male. Mean patient age was 60.8±22.67 (12-94) years. Seven (46.7%) of 15 eyes underwent a secondary IOL implantation in the same session as IOL extraction, whereas eight eyes were planned to undergo a secondary IOL implantation in a second session. Meanwhile, 2 (13.3%) eyes did not undergo IOL implantation. Median preoperative BCVA was 1.7 (0.4-1.92) logMAR and median postoperative BCVA was 0.5 (0-2) logMAR across all patients (p=0.002). After surgery, BCVA was higher in 12 patients (80%), unchanged in 2 patients (13.3%) and lower in one patient (6.7%). In our series, 3 eyes were detected to have preoperative RD and 2 eyes high IOP, whereas one patient showed recurrent RD and 4 eyes showed high IOP postoperatively. Median postoperative BCVA was significantly higher in patients who underwent secondary IOL implantation in a second session than those who underwent IOL implantation in the same session (p=0.035).Conclusion: PPV is a safe method for achieving successful visual and anatomical outcomes in patients with IOL dislocated into the vitreous cavity. In these patients, performing the secondary IOL implantation in a second session can result in a higher final visual acuity. Also, monitoring these complex cases closely is important in order to achieve better visual and anatomical outcomes.
Keywords: Intraocular lens; pars plana vitrectomy; retinal detachment